GE_GERICHTE C/10338/2018 vom 4. Dezember 2018 - GE Cour de justice (2018)
MAINLEVÉE DÉFINITIVE ; TITRE EXÉCUTOIRE ; DÉCISION SUR OPPOSITION ; ALLOCATION FAMILIALE | LP.80.al1; LP.81.al1; LPGA.54.al1; LPGA.54.al2; LAF.12.al2; LAF.40.al2